Green virtual topology design algorithm based on constraint-based routing - Yuan-sheng WU; Bing GUO; Yan SHEN; Ji-he WANG; Xiao-bin LIU (Tongxin xuebao)
To reduce the energy consumption of Internet core network, a formulation model for green virtual topology design (GVTD) problem was developed, which employs the following measures: traffic aggregation, network resources allocation on demand, virtual topology design dynamically and multi-granularity sleeping. A heuristic algorithm base on constraint-based routing, namely CBR-GVTD, was proposed, which combines the single-hop and multi-hop routing to establish virtual topology, and makes trade-offs between the network power consumption and routing performance via the constraint-based routing mechanism. The simulation results indicate that CBR-GVTD can achieve at most 62%～90% power saving with very high resource utilization (80%～90% for interface utilization) and excellent routing performance (not more than 5 for maximum routing hops).